Suppression of the Shear Raman Mode in Defective Bilayer MoS2 - Nicolosi, Valeria; Mc Evoy, Niall; Zhang, Hongzhou (My University, 2019)
We investigate the effects of lattice disorders on the low frequency Raman spectra of bilayer MoS 2. The bilayer MoS 2 was subjected to defect engineering by irradiation with a 30 keV He + ion beam, and the induced morphology change was characterized by transmission electron microscopy. When increasing the ion dose, the shear mode is observed to red-shift, and it is also suppressed sharply compared to other Raman peaks. We use the linear chain model to describe the changes to the Raman spectra. Our observations suggest that the crystallite size and orientation are the dominant factors behind the changes to the Raman spectra.
PUBLISHED
Keywords: Linear chain model; Lattice disorders; Transmission electron microscopy; Raman spectra